Release of GLP-1 and PYY in response to the activation of G protein-coupled bile acid receptor TGR5 is mediated by Epac/PLC- pathway and modulated by endogenous H2S - Bala, Vanitha; Rajagopal, Senthilkumar; Kumar, Divya P.; Nalli, Ancy D.; Mahavadi, Sunila; Sanyal, Arun J.; Grider, John R.; Murthy, Karnam (Frontiers in Physiology, 2014)
Activation of plasma membrane TGR5 receptors in enteroendocrine cells by bile acids is known to regulate gastrointestinal secretion and motility and glucose homeostasis. The endocrine functions of the gut are modulated by microenvironment of the distal gut predominantly by sulfur-containing bacteria of the microbiota that produce H2S. However, the mechanisms involved in the release of peptide hormones, GLP-1 and PYY in response to TGR5 activation by bile acids and the effect of H2S on bile acid-induced release of GLP-1 and PYY are unclear. In the present study, we have identified the signaling pathways activated by the bile acid receptor TGR5 to mediate GLP-1 and PYY release and the mechanism of inhibition of their release by H2S in enteroendocrine cells. The TGR5 ligand oleanolic acid (OA) stimulated Gs and cAMP formation, and caused GLP-1 and PYY release. OA-induced cAMP formation and peptide release were blocked by TGR5 siRNA. OA also caused an increase in PI hydrolysis and intracellular Ca2+. Increase in PI hydrolysis was abolished in cells transfected with PLC-ε siRNA. 8-pCPT-2’-O-Me-cAMP, a selective activator of Epac, stimulated PI hydrolysis, and GLP-1 and PYY release. L-Cysteine, which activates endogenous H2S producing enzymes cystathionine--lyase and cystathionine--synthase, and NaHS and GYY4137, which generate H2S, inhibited PI hydrolysis and GLP-1 and PYY release in response to OA or 8-pCPT-2’-O-Me-cAMP. Propargylglycine, an inhibitor of CSE, reversed the effect of L-cysteine on PI hydrolysis and GLP-1 and PYY release. We conclude: i) activation of Gs-coupled TGR5 receptors causes stimulation of PI hydrolysis, and release of GLP-1 and PYY via a PKA-independent, cAMP-dependent mechanism involving Epac/PLC-/Ca2+ pathway, and ii) H2S has potent inhibitory effects on GLP-1 and PYY release in response to TGR5 activation, and the mechanism involves inhibition of PLC-/Ca2+ pathway.